A before-after-control-impact study of wildlife fencing along a highway in the Canadian Rocky Mountains - Ford, Adam T.; Dorsey, Benjamin; Lee, Tracy S.; Clevenger, Anthony P. (Frontiers in Conservation Science, 2022)
Wildlife exclusion fencing has become a standard component of highway mitigation systems designed to reduce collisions with large mammals. Past work on the effectiveness of exclusion fencing has relied heavily on control-impact (i.e., space-for-time substitutions) and before-after study designs. These designs limit inference and may confound the effectiveness of mitigation with co-occurring process that also change the rate of collisions. We used a replicated (n=2 sites monitored for over 1000 km-years combined) before-after-control-impact study design to assess fencing effectiveness along the Trans-Canada Highway in the Rocky Mountains of Canada. We found that collisions declined for common ungulates species (elk, mule deer and white-tailed deer) by up to 96% but not for large carnivores. The weak response of carnivores is likely due to combination of fence intrusions and low sample sizes. We calculated realized fencing effectiveness by applying the same change in collision rates observed at control (unfenced) sites as the expected change for adjacent fenced sections. Compared to the apparent fencing effectiveness (i.e., the difference in WVCs rates before and after fencing was installed), the realized estimates of fencing effectiveness declined by 6% at one site and increased by 10% at another site. When factoring in the cost of ungulate collisions to society, fencing provided a net economic gain within 1 year of construction. Over a 10-year period, fencing would provide a net economic gain of >$500 000 per km in reduced collisions. Our study highlights the benefits of long-term monitoring of road mitigation projects and provides evidence of fencing effectiveness for reducing wildlife-vehicle collisions involving large mammals.